Challenges and Supports for Enhancing Teacher Professionalism in Private High Schools of Malang: A Qualitative Study - Ralaivao Hanginiaina Emynorane; Muhammad Huda; I Nyoman Sudana Degeng; Achmad Supriyanto; Yudin Citriadin (STAI Hubbulwathan Duri, 2024)
This study aims to identify the key constraints that undermine teacher professionalism in private high schools in Malang, as well as the support provided by school foundations to address these issues. This study uses a descriptive-qualitative method and involves 18 teachers from three private high schools in Malang. Data were collected through field observations, in-depth interviews, and documentation and analyzed in two phases: individual and cross-case analysis, ensuring validation through a member check stage. Findings reveal that teacher constraints include issues related to school policies, bureaucracy, learning process inefficiencies, and inadequate welfare. Conversely, support mechanisms from school foundations include enhanced learning facilities, professional development opportunities, scholarship provisions, and improved social welfare benefits. These findings suggest that addressing both institutional constraints and support systems is crucial in fostering an environment conducive to professional development and efficacy among teachers.